Integration of human computer interaction in architectural practice on building energy during schematic design - Mohd Ibrahim, Nor Shahrene (2012)
A complex computational calculation is involved to predict the energy performance level of a building; therefore, an ideal practice is to adopt Building Energy Simulation (BES) as a prediction tool for architects to make sustainable design decisions during Schematic Design Phase (SDP). However, this application is still not prevalent amongst architects in Malaysia especially for Jabatan Kerja Raya (JKR- Public Works Department) architects. An acceptance of BES in the JKR Architects’ Design Practice will lead to the improvement of many government’s buildings energy performance and significant measurable impacts towards Malaysian Government’s energy saving policy. While energy standards and policies deal with key planning, there is no guideline to those designing for energy performance buildings. The main objective of this research is to develop a flexible design workflow for JKR architects to use BES during SDP. Consequently, this study has integrated literature review and presented a table of three categories of BES barriers; Functional Performance, Requirements in Architectural Design and Design Workflow Process. The categories have been broken down further to pose the proposition that BES could be practised successfully by JKR architects when functional performance evaluation is made a prerequirement during design workflow process. In order to test this theoretical proposition, this research has reviewed existing documents to analyse BES procedure and JKR architects’ current design practices during SDP. An interview was carried out with several JKR architects to determine the barriers towards employing BES,while simulation was performed to identify the technical procedure in BES application. The results and analyses of the BES procedure and JKR design practice found similarities in term of the process performed by the actor: objective, structure & tool and output. A workflow model using HCI’s ActionWorkflow Theory found that both BES procedure and JKR design process can co-exist within a process loop during SDP. The research has addressed some of the unsolved problems in the architectural design process where there is a complex phenomenon that involves architect’s experience, knowledge and background (qualitative/ artistic) and the effects of an intervention – building performance evaluation which is more quantitative and technical in nature. The benefit of this study includes formalisation of a BES and JKR architects integrated workflow process which recommends practice guidelines for JKR architects to employ BES during SDP. These results are expected to lead towards the advancement of new knowledge by enhancing the design process using BES Procedure – JKR Architects Workflow Process whereby BES is accepted by JKR architects to predict building performance in term of energy use and environmental and sustainable practices.